Mesenchymal Stromal Cell Uses for Acute Kidney Injury—Current Available Data and Future Perspectives: A Mini-Review - Zilberman-Itskovich, Shani; Efrati, Shai (Frontiers in Immunology, 2020)
There is growing evidence concerning the potential use of mesenchymal stromal cells (MSCs) for different tissue injuries. Initially, the intended physiological use of MSCs was due to their ability to differentiate and replace damaged cells. However, MSCs have multiple effects, including being able to significantly modulate immunological responses. MSCs are currently being tested for neurodegenerative diseases, graft versus host disease, kidney injury and other chronic unremitting tissue damage. Using MSCs in acute tissue damage is only now being studied. Acute kidney injury (AKI) is a common cause of morbidity and mortality. After the primary insult, overactivation of the immune system culminates in additional secondary potentially permanent kidney damage. MSCs have the potential to ameliorate the secondary damage and recent studies have shed important light on their mechanisms of action. This article summarizes the basics of MSC therapy, the newly discovered mechanisms of action and their potential application in the setting of AKI.